Brownshirt princess : a study of the "Nazi Conscience" - Gossman, Lionel (Open Book, 2009)
"Princess Marie Adelheid of Lippe-Biesterfeld was a rebellious young writer who became a fervent Nazi. Heinrich Vogeler was a well-regarded artist who was to join the German Communist Party. Ludwig Roselius was a successful businessman who had made a fortune from his invention of decaffeinated coffee. What was it about the revolutionary climate following World War I that induced three such different personalities to collaborate in the production of a slim volume of poetry -- entitled Gott in mir -- about the indwelling of the divine within the human? Lionel Gossman's study situates this poem in the ideological context that made the collaboration possible. The study also outlines the subsequent life of the Princess who, until her death in 1993, continued to support and celebrate the ideals and heroes of National Socialism"--Publisher's description